الصورة التشبيهية في نهج البلاغة - الهلال، خليل عبدالسادة إبراهيم; سعيد، حوراء عبد علي (جامعة الكوفة - كلية الآداب, 2016)
وبعد هذه الجولة البحثية في (الصورة التشبيهية في نهج البلاغة) وجد البحث ما يلي: يعد التشبيه عند العرب من بين فنون البلاغة الأخرى مساحة واسعة لأنها من أقرب الصور البلاغية إيضاحا وافهاما في تصوير المشهد الحسي، بطريقة يجعل المتلقي يري حقيقة تلك الصورة وكأنها عاشها وأدرك مضامينها بكامل جزئياتها فقد احتلت الصورة التشبيهية في نصوص الأمام على بالمشاهد المحسوسة الحية، تنوعت ما بين خطب ورسائل وحكم قصار، فعمد الإمام علي بالتشبيه الحسي في تعزيز وترسيخ الصورة في ذهن المتلقي، لآن التشبيه من بين فنون البلاغية الأخرى لا يحتاج من المنشئ إلي بذل جهد في استجلاء المعني للمتلقي خصوصا في المواقف الخطابية الحربية، لذا استعان بها الإمام علي في دعم وترسيخ الفكرة في أذهانهم.
The analogy between the Arabs of other arts of rhetoric and wide areaBecause it is the nearest of images and rhetorical clarification Affhamaln the fdming of the scene sensoryA way that makes the recipient sees the fact that pictureAs if they lived and realize the full implications fractions Image has occupied the simulations in the texts of Imam Ali(peace be upon him)Live scenes perceived, including familiarity different aspects of life, including faith-based, social and economic Varied between speeches and letters and the rule of Kassar, have resorted Imam Ali(peace be upon him)sensory analogy in the promotion and consolidation of the picture in the mind of the recipient; because of the analogy between the rhetorical arts Otherlt does not require the originator to make an effort to elucidate the meaning of the recipients, especially in situations of war rhetoricSo hired by Imam Ali (peace be upon him) at the support and the consolidation of the idea in their minds.
Keywords: اللغة العربية -- البلاغة العربية -- التشبيه -- الصورة التشبيهية -- الهاشمي، علي بن أبي طالب بن عبد المطلب، 40 هـ